An Empirical Study of The Factors Affecting University Students’ Satisfaction Towards Foodpanda Mobile Application - Sabeh, Hala Najwan; Gulati, Chanda; Aronkar, Praveen; Lim, Jia Yun; Liew, Qian Yee; Lim, Lun Hau; Lim, See Ai; Achmad, Daffa Abiyyu; Tomar, Sony; Jain, Muskan; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
Foodpanda is a well-known online food delivery platform. Foodpanda has evolved to be a popular option for individuals looking for simple and convenient food delivery services, particularly university students. The objectives of this study are to provide novel insights and investigate what factors influence university students' satisfaction with the Foodpanda mobile application through the proposed research model. Precisely, the objective of this article is to examine the relationship between information quality, system quality, price, perceived convenience, delivery experience, and customer satisfaction. The results of this study aim to guide Foodpanda managers in ensuring a high degree of customer satisfaction and retention, as customer satisfaction is critical to a company's success. This study will use a quantitative method to obtain data from university students by administering a survey. SPSS software will be used to analyze the collected data. Based on the findings, it is anticipated that the five investigated factors will have significant effects on customer satisfaction.